2021
DOI: 10.3389/frobt.2021.576783
|View full text |Cite
|
Sign up to set email alerts
|

3D Scanning of the Forearm for Orthosis and HMI Applications

Abstract: The rise of rehabilitation robotics has ignited a global investigation into the human machine interface (HMI) between device and user. Previous research on wearable robotics has primarily focused on robotic kinematics and controls but rarely on the actual design of the physical HMI (pHMI). This paper presents a data-driven statistical forearm surface model for designing a forearm orthosis in exoskeleton applications. The forearms of 6 subjects were 3D scanned in a custom-built jig to capture data in extreme pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In this study, there are 55 UC-ITN patients with NVC on the unaffected side, indicating that the presence of NVC did not necessitate the UC-ITN condition. The results showed that SALGLE (19), Coarseness (20), MAL (21), DV (22), Maximum (23), Correlation (17), and the Ofv were the risk factors for UC-ITN with bilateral NVC. UC-ITN patients with bilateral NVC only suffered from unilateral pain, probably due to different degrees of trigeminal degeneration and demyelination between the affected and unaffected side, which might lead to changes in the above-mentioned texture features.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, there are 55 UC-ITN patients with NVC on the unaffected side, indicating that the presence of NVC did not necessitate the UC-ITN condition. The results showed that SALGLE (19), Coarseness (20), MAL (21), DV (22), Maximum (23), Correlation (17), and the Ofv were the risk factors for UC-ITN with bilateral NVC. UC-ITN patients with bilateral NVC only suffered from unilateral pain, probably due to different degrees of trigeminal degeneration and demyelination between the affected and unaffected side, which might lead to changes in the above-mentioned texture features.…”
Section: Discussionmentioning
confidence: 95%
“…To optimize the pHMI fit, a design approach could be to account for human anthropometric heterogeneity and changes in volume during movement by performing anthropometric studies specifically tailored to the body region of a certain interface with the aid of 3D shape analysis [55,61]. In a second step, it is necessary to ensure that interfaces remain in position, either through active control (active exoskeletons) [62,63] or biomechanical measurements of relative movements (passive exoskeletons) [50].…”
Section: Considerations On the Design Of Phmismentioning
confidence: 99%
“…Digital representations of anatomical structures play a crucial role in various applications within the biomedical field. For example, an accurate 3D model depicting the anatomy of the upper limb can be utilized to design customized devices for personalized rehabilitation or human–machine interfaces (HMIs) [ 1 ]. Enhancing upper limb functionality holds immense importance for patients afflicted with sports injuries, strokes, or dystonia disorders, as the upper limb is extensively involved in daily activities.…”
Section: Introductionmentioning
confidence: 99%